What’s in a place? The contribution of strategic communication to placemaking and territorial communication - Duarte Melo, Ana (2021)
Set in the field of territorial communication, the aim of this chapter is to summon the various contributions of strategic communication to placemaking and promotion, approaching them both through a mind frame path, as a multi-layered concept, and through an operational approach, as a pragmatic tool. Going through a number of examples we will reflect on several experiences to illustrate the potential of strategic communication to add value to places in different sets and scales, from building a place almost from scratch to nation branding strategies, from positioning and re-positioning objectives to building up notoriety or developing communities’ sense of belonging to a territory. We also set an evolutionary frame of the territorial communication in the light of its strategic dimension, drawing on key concepts and trends, influences and achievements. The performative value of strategic communication as a constructive tool of territorial development is discussed in addition to the communicational added value of territorial brands, namely by pointing emerging issues such as storytelling or participatory place communication. Furthermore, we summon ethical and pragmatic challenges to the debate as inspiration for future research.